Prediction of mechanical behaviour of inhomogeneous and anisotropic materials using an incremental scheme (Archives of Mechanics - Test, 2000)
A new multisite homogenisation technique is proposed, suitable for the description of the effective properties of composite materials. After a short presentation of the multisite approach, the traditional self-consistent approximation is developed. The limitations of such an approach are emphasised and a new alternative technique, based on the differential scheme idea, is proposed. The great versatility of this method in predicting the global elastic properties of various inhomogeneous materials is demonstrated. The present examples correspond to extreme situations of composites with voids and that of quasi-rigid (compared to the matrix) reinforcements. Very good agreement between the predicted and measured (or calculated by FEM) equivalent properties are found.